E01 CAG Repeat Length Predicts Rate of Striatal Atrophy, but Relationship is Nonlinear. (17th September 2014) - Aylward, E; Long, JD; MacDonald, ME; Lee, J-M; Paulsen, J; Gusella, J
Abstract : Background: Previous cross-sectional and longitudinal research suggests that HD clinical progression and striatal atrophy occur at a faster rate in individuals with higher CAG repeat lengths. This has led to discussion regarding the possibility that individuals with higher CAG repeat lengths might make good candidates for clinical trials, as disease-slowing effects of treatment could be more quickly demonstrated in individuals whose natural rate of progression is faster. Aims: The current study was designed to determine whether the relationship between CAG repeat length and rate of atrophy in caudate and putamen is linear, with rates of progression continuing to increase as CAG repeat lengths increase. Methods: Participants were 990 gene-expanded individuals from the PREDICT-HD study with 39 to 50 CAG repeats (mean CAG = 42.5; mean age = 39.9 years, mean years in study = 4.8). For each participant, the slope of caudate and putamen volume change (corrected for intracranial volume) was calculated, using all longitudinal data available for that subject. Linear mixed models were used, controlling for age, with particular interest in the analysis of slope changes as a non-linear (quadratic) function of CAG. Results: Consistent with previous studies, correlations between CAG repeat length and longitudinal rate of change were significant for caudate and putamen volumes. Furthermore, results indicated a highly significant interaction for Year × CAG 2 for putamen, indicating that the putamen slope increases with higher CAG repeat length, but that this increase ceases to escalate for CAG lengths in the higher range (˜46+). The Year × CAG 2 interaction showed a trend toward significance for caudate. Conclusions: Results of this study suggest that inclusion of individuals with higher CAG repeat length in clinical trials may be a good strategy, but efforts to enrich the sample with very high CAG repeat lengths (> 46) will not further increase the efficiency of clinical trials.